THE ASSOCIATION BETWEEN LEVEL OF KNOWLEDGE AND CONSUMPTION OF IFA SUPPLEMENTATION IN ADOLESCENT GIRLS: A CASE STUDY IN SIDOARJO REGENCY - Riesmiyatiningdyah; Farhan Ardiansyah; Tamara Nur Budiarti (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Anemia in adolescent girls remains a significant health problem, primarily due to iron deficiency. One preventative measure is the administration of iron supplements (TTD). However, compliance with iron supplements (TTD) among adolescent girls remains suboptimal. Knowledge is suspected to be a factor influencing consumption behavior. Purpose: This study aims to determine the relationship between the level of knowledge about iron supplements and the consumption of iron supplements in adolescent girls. Methods: This research method used a quantitative design with a cross-sectional approach. The population are adolescent girls in Sidoarjo. A sample of 106 respondents was drawn using a probability sampling technique with a multistage sampling method. Data were collected using a questionnaire and analyzed using the Chi-Square test with a significance level of 0.05. Results: The results showed that most respondents had a good level of knowledge (41.5%) and were compliant in taking iron tablets (54.7%). The Chi-square test showed a p-value of 0.001 (<0.05), indicating a significant relationship between knowledge level and iron tablet consumption. Conclusion: This study concluded that there was a relationship between knowledge about iron supplements and their consumption among adolescent girls. Increasing knowledge can be an important strategy for improving adherence to iron supplements.